Strategic plan for Intercrafts Perú - Hein, Walter (2015)
Intercrafts Peru Inc. has been working side by side with Peruvian handcrafts producers for over ten years and it is currently going through a financial and organizational downturn. The company has experienced net losses for the past three years and there is a need to implement changes that can revert this situation by putting the company back on track to achieve sustainable long term grow. The organization is subjected to trade practices established by the World Fair Trade Organization (WFTO) and it is through this practices that the company has established long term relationships with customers in North America, Europe and Oceania. However changes in the industry and internal inefficiencies limit the capacity of Intercrafts to increase the number of sales reaching new customers. The company was born as an initiative of the (Interregional Central of Peruvian Artisans) CIAP and explains the low bargaining power towards the suppliers because of the relationship. Furthermore this bond reinforces the social commitment of the organization from its conception, to support the sustainable development of the artisans and their environment. It is in this commitment that the company can exploit most of the potential strengths and opportunities. In this context this strategic plan proposes the use of three strategies to take the company from its current situation to the desired situation to be the best crafts exporting company in Peru in 2020: (a) Product development through strategic alliances, creating new designs capacitating the artisans to improve the products; (b) Retrenchment, restructuring some of the company’s processes to reduce costs and have an efficient operational system; and (c) Market penetration attacking the high end niche market with improved marketing.